Biomarkers of sarcopenia in very old patients with hip fracture. Issue 2 (8th January 2020) - Sánchez‐Castellano, Carmen; Martín‐Aragón, Sagrario; Bermejo‐Bescós, Paloma; Vaquero‐Pinto, Nieves; Miret‐Corchado, Carmen; Merello de Miguel, Ana; Cruz‐Jentoft, Alfonso José
Abstract: Background: Hip fracture is both a cause and a consequence of sarcopenia. Older persons with sarcopenia have an increased risk of falling, and the prevalence of sarcopenia may be increased in those who suffer a hip fracture. The aim of this study was to explore potential biomarkers (neuromuscular and peripheral pro‐inflammatory and oxidative stress markers) that may be associated with sarcopenia in very old persons with hip fracture. Methods: We recruited 150 consecutive patients ≥80 years old admitted to an orthogeriatric unit for an osteoporotic hip fracture. Muscle mass was assessed pre‐operatively using bioelectrical impedance analysis; Janssen's (J) and Masanés' (M) reference cut‐off points were used to define low muscle mass. Muscle strength was assessed with handgrip strength (Jamar's dynamometer). Sarcopenia was defined by having both low muscle mass and strength and using the European Working Group on Sarcopenia in Older People 2 definition of probable sarcopenia (low grip strength). Peripheral markers—pro‐inflammatory and oxidative stress parameters—were determined either in the plasma or in the erythrocyte fraction obtained from peripheral whole blood of every patient pre‐operatively. Results: Mean age was 87.6 ± 4.9 years, and 78.7% were women. The prevalence of sarcopenia was 11.5% with Janssen's, 34.9% with Masanés' cut‐offs, and 93.3% with the European Working Group on Sarcopenia in Older People 2 definition of probable sarcopenia. Among the four pro‐inflammatory cytokines tested in plasma, only tumour necrosis factor‐α was different (lower) in sarcopenic than in non‐sarcopenic participants using both muscle mass cut‐offs (J 7.9 ± 6.2 vs. 8.3 ± 5.8, M 6.8 ± 4.7 vs. 9.1 ± 6.2). Erythrocyte glutathione system showed a non‐significant tendency to lower glutathione levels and glutathione/oxidized glutathione ratios in sarcopenic participants compared with non‐sarcopenic subjects. Catalase activity was also lower in sarcopenic participants (J 2904 ± 1429 vs. 3329 ± 1483, M 3037 ± 1430 vs. 3431 ± 1498). No significant differences were found between groups in chymotrypsin‐like activity of the 20S proteasome, superoxide dismutase, glutathione peroxidase and butyrylcholinesterase activity, C‐terminal agrin fragment, interferon‐γ, or interleukin‐1β. Conclusions: The prevalence of sarcopenia in patients with hip fracture varies according to the definition and the muscle mass reference cut‐off points used. We did not find differences in most neuromuscular, pro‐inflammatory, or oxidative stress markers, except for lower peripheral tumour necrosis factor‐α levels and catalase activity in sarcopenic participants, which may be markers of an early inflammatory reaction that is hampered in sarcopenic patients.